Impact of COVID-19 on sexual and reproductive health - Soria Gonzales, Lalescka Araceli (2021)
Peru is going through a pandemic originated by coronavirus disease (COVID-19) and we continue to maintain mandatory social isolation as a preventive measure to reduce infections.Due to this event, many health establishments had to suspend care, also affecting Sexual and Reproductive Health (SRH) services, especially external consultation services. Due to this event, many health establishments had to suspend their attention , also affecting Sexual and Reproductive Health (SRH) services, especially external consultation services. Limited access to those services would increase the rate of unwanted pregnancies, abortions, sexually transmitted infections (STIs), complications during pregnancy, intimate partner violence, and maternal and infant mortality